2012
DOI: 10.1002/jgt.21673
|View full text |Cite
|
Sign up to set email alerts
|

Fire Containment in Planar Graphs

Abstract: In a graph G, a fire starts at some vertex. At every time step, firefighters can protect up to k vertices, and then the fire spreads to all unprotected neighbours. The k-surviving rate ρ k (G) of G is the expectation of the proportion of vertices that can be saved from the fire, if the starting vertex of the fire is chosen uniformly at random. For a given class of graphs G we are interested in the minimum value k such that for some constant ǫ > 0 and all G ∈ G, ρ k (G) ≥ ǫ (i.e., such that linearly many vertic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…Noting the results on the 2‐surviving rate for planar graphs without 3‐, 4‐, 5‐, or 6‐cycles, respectively , one may ask the following question: Problem Does it exist a function f:Nfalse{1,2false}double-struckR+ such that for any k3 and any nontrivial planar graph G without k ‐cycles there is ρ2false(Gfalse)>ffalse(kfalse)?…”
Section: Remarksmentioning
confidence: 99%
See 3 more Smart Citations
“…Noting the results on the 2‐surviving rate for planar graphs without 3‐, 4‐, 5‐, or 6‐cycles, respectively , one may ask the following question: Problem Does it exist a function f:Nfalse{1,2false}double-struckR+ such that for any k3 and any nontrivial planar graph G without k ‐cycles there is ρ2false(Gfalse)>ffalse(kfalse)?…”
Section: Remarksmentioning
confidence: 99%
“…It has been shown that 2 is the upper bound for triangle‐free planar graphs and planar graphs without 4‐, 5‐, or 6‐cycles , respectively. In particular Esperet et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of this concept has become very fruitful in the literature and the evidence is the existence of many works on the subject for different graph structures [9,6,14,16,29,36,41,44,42,43].…”
Section: Introductionmentioning
confidence: 99%